A coupled DEM-SPH model for moisture migration in unsaturated granular material under oscillation. (1st March 2020) - Chen, Jian; Orozovic, Ognjen; Williams, Kenneth; Meng, Jingjing; Li, Chengzhi
Highlights: Coupled DEM-SPH model for unsaturated dynamic moisture migration and coded program. Conducted experiments on spherical and non-spherical materials. Simulation model provided good agreement with experiments for both cases. Abstract: Granular materials, such as mineral products, soil and chemical fertilizer, normally contain unsaturated free moisture. This unsaturated moisture could migrate in the granular material and its processing, resulting in handling and safety concerns due to a change in the material properties. In this work, a method of coupling the Discrete Element Method (DEM) and the Smoothed Particle Hydrodynamics (SPH) was proposed to investigate moisture migration in unsaturated granular materials under oscillation. The particles and water were simulated through DEM and SPH, respectively and a python coupling framework was programmed to perform the exchange of particle-fluid interaction forces. Subsequently, experiments with plastic pellets and a coal sample were used to calibrate the models, with DEM calibrated by an angle of repose experiment and draining experiments calibrating the coupled model. Finally, the coupled model was validated by comparing the results to those of experiments involving moisture migration under oscillation. It was found that, compared to measurements, the coupled SPH-DEM model predicted the same moisture migration trend and also provided good agreement for the prediction of the mass of drained water. Graphical abstract: Image, graphical abstract